Waldo Peirce papers - Peirce, Waldo, 1884-1970.
Chiefly correspondence as well as a diary, poems, financial records, and other papers. Family correspondence includes many letters between Peirce and his mother, Anna Hayford Peirce. His letters are often illustrated with pen and ink drawings and trace the development of his artistic career and her letters describe her travels and life in Bangor, Me. School papers from Peirce's years at Harvard University include his pen and ink drawings along with comments of Charles Townsend Copeland. Other correspondents include Peirce's brother Hayford Peirce, and George Biddle, Lincoln Colcord, Douglas W. Gorsline, Marsden Hartley, Ernest Hemingway, Earnest Albert Hooton, Dahlov Zorach Ipcar, Doris Lee, Samuel Eliot Morison, Maxwell E. Perkins, Henry V. Poor, Homer Saint-Gaudens, Millard Sheets, Frederic Taubes, Hendrik Willem Van Loon, Art Young, and William Zorach.
Microfilm edition of scrapbooks (1935-1937, 1940-1941) available
Microfilm edition of booklets titled "Alphabets Intimes" and "Le Mariage de Suzanne" available
Microfilm edition produced from originals in Manuscript Division.
Library of Congress Prints and Photographs Division.
Artist.
Collection material in English and French.
Keywords: Biddle, George, -- 1885-1973 -- Correspondence; Colcord, Lincoln, -- 1883-1947 -- Correspondence; Copeland, Charles Townsend, -- 1860-1952.; Gorsline, Douglas W., -- 1913-1985 -- Correspondence; Hartley, Marsden, -- 1877-1943 -- Correspondence; Hemingway, Ernest, -- 1899-1961 -- Correspondence; Hooton, Earnest Albert, -- 1887-1954 -- Correspondence; Ipcar, Dahlov Zorach, -- 1917- -- Correspondence; Lee, Doris, -- 1905-1983 -- Correspondence; Morison, Samuel Eliot, -- 1887-1976 -- Correspondence; Peirce, Anna Hayford, -- 1856-1928 -- Correspondence; Peirce, Hayford, -- 1883-1946 -- Correspondence; Perkins, Maxwell E. -- 1884-1947 -- Correspondence; Poor, Henry V. -- 1812-1905 -- Correspondence; Saint-Gaudens, Homer, -- 1880- -- Correspondence; Sheets, Millard, -- 1907- -- Correspondence; Taubes, Frederic, -- 1900-1981 -- Correspondence; Van Loon, Hendrik Willem, -- 1882-1944 -- Correspondence; Young, Art, -- 1866-1943 -- Correspondence; Zorach, William, -- 1887-1966 -- Correspondence; Pierce family; Pierce family -- Correspondence; Harvard University -- Students; Art; Art, American -- 20th century; Voyages and travels; Bangor (Me.) -- Social life and customs; Maine -- Social life and customs; Artists